Hitchhiker : Stories from the Kentucky Homefront - Thompson, Bob, 1950 August 8- (Book collections on Project MUSE., 2017)
"Growing up next door to his Granny's country store in McCracken County, Kentucky, a very young Bob Thompson had unlimited access to the cold-drink box and shelves of candy. Only later did he realize that the greatest benefit of this arrangement was that his playmates and best friends were all adults who frequented the grocery. As he passed his childhood years on the store's front porch, Thompson internalized the tales and folk traditions conveyed by his grandmother and her customers. These moments allowed him to discover his own passion for storytelling. In Hitchhiker: Stories from the Kentucky Homefront, Thompson offers readers homegrown tales that interweave ghosts of the past with real and imagined worlds. The stories progress from his Tom Sawyer-esque childhood in Western Kentucky through his various incarnations as everything from an incense-burning flower-child hitchhiker to an unrepentant adventurer following the footsteps of Hemingway and the Lost Generation across Europe. This collection brings together coming-of-age tales, family stories of bygone eras, and even true accounts of unsolved murders and mysteries. Hitchhiker is Huckleberry Finn meets The Twilight Zone, with just a taste of The Electric Kool-Aid Acid Test. It is a book that will make you wish you'd paid closer attention to your grandparents' and parents' stories and photo albums, that you'd been less cautious and traveled more, that you'd followed your heart and made time to search for your guides and kindred spirits"--